Legal Protection of Intellectual Property Rights in Rural Village in Subdistrict Sekaran Lamongan District - Sutrisno; Adhitya Widya Kartika (Nusantara Science and Technology Proceedings)
This Research is Owned by Enterprises Villages and their management in Intellectual Property Rights are important to study. This law hopes that villages can develop more than before. The village is expected to develop through the management of village funds into village-owned enterprises. This management can be in the form of making products of the effectiveness and creativity of the community which is then registered as Intellectual Property Rights so that a village has different characteristics from other villages which certainly gives added value to this village. Success in management can be achieved if the village government and the community can understand the legal processes and rules for managing Intellectual Property Rights, so this becomes important. This research was conducted to ensure that the implementation of Village-Owned Enterprises and the management of Intellectual Property Rights in village products can be carried out properly following applicable norms. This research was conducted by socio-legal research methods by analyzing primary and secondary data to find conclusions. The results of the study stated that many villages that have been studied do not understand Intellectual Property Rights so that no village products or village communities are registered with Intellectual Property Rights. There is even concern for the community that causes community products not to be included in the Village Owned Enterprises related to revenue sharing.